Pelayanan Pembuatan Surat Izin Mengemudi Golongan C bagi Masyarakat Manggarai Timur - Elisabet Clara Yunita; Umbu Lily Pekuwali; Norani Asnawi (JURNAL RISET RUMPUN ILMU PENDIDIKAN, 2025)
This research is based on the fact that in the process of making a Driving License, the Manggarai Timur Community is faced with serious challenges, considering that until now the Manggarai Timur Police have not provided this service, forcing the Manggarai Timur community to travel to Ruteng, Polres Manggarai to take care of their SIM. Long trips not only take a lot of time but also cost a lot of money for the community, especially for those who live in remote areas in the Manggarai Timur area. The type of research used is empirical legal research. Data Collection Techniques interviews, observations and documentation. The results of this study indicate that the aspects of the SIM C making service for the Manggarai Timur community at the Manggarai Polres Traffic Unit, include; Accessibility of SIM C making services at the Manggarai Polres, Speed ​​​​in the SIM C Making Process, and the Level of Satisfaction and Perception of the Manggarai Timur Community Regarding the Services Provided Driving License services at the Manggarai Polres Traffic Unit are quite adequate, they only need to be improved. Meanwhile, the factors that influence the service for making Class C Driving Licenses for the people of East Manggarai at the Manggarai Police Traffic Unit include the availability of facilities and infrastructure, geographical conditions or environmental factors, the existence of complex and complicated requirements that must be met in the application and making of Class C Driving Licenses, the number of officers available to serve Class C Driving License applications, and the potential for corrupt practices or illegal levies that can hinder the process of making Class C Driving Licenses efficiently and transparently.